Correlation for the viscosity of methane (CH4) from the triple point to 625 K and pressures to 1000 MPa - Sotiriadou, Sofia; Antoniadis, Konstantinos D.; Assael, Marc J.; Martinek, Viktor; Huber, Marcia L. (International journal of thermophysics, 2026)
A wide-ranging model for the viscosity surface of methane (CH4) was developed with a range of validity from the triple-point temperature to 625 K and pressures up to 1000 MPa. An extensive literature survey was undertaken and all available experimental data, to the extent of our knowledge, were considered in the development of the model. The correlation incorporates recent ab initio results for the dilute-gas contribution, Rainwater-Friend theory for the initial density dependence, and an empirical contribution for higher densities obtained using recently developed open-source symbolic regression software. The estimated uncertainty of the correlation (at k = 2) varies from a low of 0.13 % for the gas at pressures below 1 MPa over temperatures from 210 K to 392 K, to 0.8 % to 2 % depending on the temperature for the mid-pressure range of 1 MPa < p < 50 MPa, and is 4 % for pressures from 50 MPa to 1000 MPa for temperatures from 223 K to 625 K. In the liquid region at pressures up to 33 MPa, the estimated uncertainty is 3 %.
Online veröffentlicht: 08. Dezember 2025
Gesehen am 26.02.2026
Im Titel ist die Zahl "4" tiefgestellt